Economic evaluation of protein recovery process from Argentinian soybean extruded-expelled meals = Evaluación económica del proceso de recuperación de proteínas de las harinas extraídas de la soja argentina - Accoroni, Cecilia (2022)
Soybean extruded-expelled (EE) meals are the byproduct of the soybean oil extraction process commonly used by small and medium- sized Argentinean companies. In this study, the economic feasibility of protein concentrate production from soybean EE meals was evaluated. A processing daily capacity of 18 ton of EE meals was considered, resulting in an annual production of 1,500 ton of protein concentrate. The proposed methodology considered a pH change process consisting of 3 cycles of alkaline extraction at 60 ºC followed by isoelectric precipitation at low temperature using hydrochloric acid, which resulted in a final product with a protein content of 75 % (db) and a productivity of 0.28 kg product/kg soybean EE meals. To analyze a practical case, proposed production was carried out as an extension of a typical medium-sized soybean extrusion- expelling plant. As a result, the necessary capital investment was estimated to be US$2.7 million. Additional financial performance indicators were computed, including net present value and internal rate of return, and it was concluded that the proposal to obtain a protein concentrate from soybean EE meals was economically viable on an industrial scale if sale prices are above 2,267 US$/ton.